Interprofessional collaboration and the Brazilian Sanitary Reform: implications for delivery of healthcare - Matuda, Caroline Guinoza; Aguiar, Dulce Maria de Lucena; Frazão, Paulo (Saúde e Sociedade, 2013)
The social, economic and sanitary changes in Brazil reinserted earlier problems and brought news ones for the health human resources area. Among the new challenges, it is important to underline those implicated to reorientation strategies of the health care model which has required more intensive process of professional interaction. The aim of this article was to review the knowledge related to interprofessional collaboration as a research issue highlighting its importance for understanding of the relations among workers in the production of care within Brazilian health system. Historical characteristics that marked the health sector reforms in the world and particularly in the Brazil were summed up. Based on review studies, knowledge about interprofessional collaboration were summarized focusing definitions, theoretical models and the observed results. An approach directed to comprehension of process and relations implicated to the problem is indicated in order to surmount the barriers connected to the need for a more effective, efficient and equitable health care model. For this it is necessary to admit the professional as a social agent bearer of an interested practice considering that thinking frameworks as organizations and overall structure denote social construct. The understanding of the forces that guide the interprofessional conflict and collaboration may subsidize the formulation of strategies for improving healthcare in Brazilian health system.